The Effects of Urea Fertilizing Techniques on Growth and Yield of Corn (Zea mays) in Vertisol Playen, Gunungkidul - Heny Alpandari; Eka Tarwaca Susila Putra; Cahyo Wulandari (Jurnal Ilmu Pertanian, 2019)
Corn production can be increased by proper urea fertilizers. Fertilization techniques commonly used by farmers are broadcast or buried into soil. But in both of these techniques can make to lose urea faster, because nature of urea is easily changed to ammonium (NH4+), then changed to ammonia (NH3) which leads to volatilization or leaching. This study aims to compare urea fertilization techniques commonly used by farmers and their effects on the growth and yield of corn in Vertisol on rainy season. The research method used was a single factor in randomized complete block design (RCBD) with four blocks as replications. The treatments were without urea (N1), buried urea into soil (N2), and broadcast of urea (N3), with a urea dose of 348 kg/ha obtained from soil sampling analysis. The observation of parameters (1) Climatic condition, (2) physical and chemical characters of soil, (3) Plant height, (4) Effect N fertilization on root and shoot, (5) Chlorophyll content and nitrate reductase activity, (6) observations of harvested. The data were analyzed using Analysis of Variance (ANOVA) at 5% levels, and continued Duncan Multiple Range Test (DMRT) at test level of 5%. The results showed that fertilization affecteds all parameters. Buried into soil (N2) and broadcast (N3) technique was significantly different only in leaf N content that is 3,31% (N2), 2,16% (N3) and also in higher plant, but not significantly different in other variables. Based on this research, farmers still use broadcast techniques because they are more efficient in terms of time and energy.